Impact of the cultivation strategy on resveratrol production from glucose in engineered Corynebacterium glutamicum - Braga, Adelaide; Oliveira, Joana; Silva, Rita; Ferreira, Patricia; Rocha, Isabel; Kallscheuer, Nicolai; Marienhagen, Jan; Faria, Nuno (Journal of biotechnology, 2018)
•Resveratrol production in C. glutamicum in defined medium starting from glucose.•Production was achieved in absence of p-coumaric acid and cerulenin.•Optimization of cultivation conditions in batch and fed-batch mode.•Product degradation was observed in presence of high oxygen levels.•Resveratrol degradation can be prevented in an anaerobic stationary phase. The health benefits of polyphenols such as stilbenes and flavonoids for humans are increasingly attracting attention. Resveratrol is a well-characterized naturally-occurring stilbene and potent anti-oxidant, which is used as food supplement and cosmetic ingredient. Several microorganisms including Corynebacterium glutamicum were engineered for resveratrol production from glucose. Based on the cultivation of a resveratrol-producing C. glutamicum strain in shake flasks, different strategies for improving production under controlled conditions at bioreactor scale were tested. To this end, different cultivation parameters including substrate concentration and operation modes (batch and fed-batch) were evaluated. Whereas the highest biomass concentration was observed during fed-batch fermentation, the maximum resveratrol production was achieved in batch mode. The maximal titer obtained was 12mgL−1 of resveratrol without the addition of the fatty acid synthase inhibitor cerulenin, which was previously shown to be crucial for production with C. glutamicum. The specific growth rate during production seems to have a significant effect in resveratrol production and apparently low specific growth rates may redirect the metabolic bottleneck from p-coumaric acid formation to malonyl-CoA or ATP availability. We also show that high oxygen concentrations in the bioreactor negatively affected the obtained resveratrol titers with C. glutamicum, which is most likely due to the strong tendency of resveratrol to oxidize or oligomerize. Thus, up-scaling of the resveratrol production process is technically challenging and individual process parameters have to be optimized cautiously.